1992
DOI: 10.1126/science.1523408
|View full text |Cite
|
Sign up to set email alerts
|

Carnivorous Plants: Phylogeny and Structural Evolution

Abstract: The carnivorous habit in flowering plants represents a grade of structural organization. Different morphological features associated with the attraction, trapping, and digestion of prey characterize a diversity of specialized forms, including the familiar pitcher and flypaper traps. Phylogenetic analysis of nucleotide sequence data from the plastic rbcL gene indicates that both carnivory and stereotyped trap forms have arisen independently in different lineages of angiosperms. Furthermore, these results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
181
0
6

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(202 citation statements)
references
References 45 publications
4
181
0
6
Order By: Relevance
“…Furthermore, for RNase T2, significant molecular convergence was also detected between Cephalotus and the common ancestor of the three Caryophyllales species, D. adelae, D. muscipula and N. alata, which produce sticky, snap and pitfall traps, respectively. Parsimonious inference of character evolution indicates that trapping strategy diversified after the establishment of carnivory in the Caryophyllales 3,20 . Therefore, molecular adaptation of RNase T2 probably occurred both during the evolution of carnivory and subsequently during the establishment of the specific capture strategy of pitfall traps.…”
Section: Articles Nature Ecology and Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, for RNase T2, significant molecular convergence was also detected between Cephalotus and the common ancestor of the three Caryophyllales species, D. adelae, D. muscipula and N. alata, which produce sticky, snap and pitfall traps, respectively. Parsimonious inference of character evolution indicates that trapping strategy diversified after the establishment of carnivory in the Caryophyllales 3,20 . Therefore, molecular adaptation of RNase T2 probably occurred both during the evolution of carnivory and subsequently during the establishment of the specific capture strategy of pitfall traps.…”
Section: Articles Nature Ecology and Evolutionmentioning
confidence: 99%
“…2a and Supplementary Tables 25-28). As Drosera and Nepenthes trace back to a common carnivorous origin in Caryophyllales 3,20 , the four species including Cephalotus therefore cover three independent origins of plant carnivory. Together with previously identified enzyme sequences including proteins from Dionaea (Supplementary Table 24), we inferred phylogenetic relationships among the digestive fluid proteins ( Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…numerous inter-species comparisons reveal a phylogenetic effect on phenotype. Not only have phylogenetic effects been described in plant phenotypes such as photosynthetic pathway (Ehleringer and Monson, 1993), carnivory (Albert et al, 1992), N-fixing symbioses (Doyle, 1998), mycorrhizal symbioses (Fitter and Moyerson, 1996) and ecological traits (Ackerley, 1999), but also in the uptake of 134/137 Cs Willey et al, 2005), heavy metals (Broadley et al, 2001), Al (Jansen et al, 2002), Ca and a range of nutrients . It has been noted that phylogenies might be useful to estimating radionuclide transfer to plants (Beresford et al, 2004;Willey et al, 2005).…”
Section: E-mail Addressmentioning
confidence: 99%
“…Research on functional responses can be traced back to the early 19th century [9] and the body of knowledge in the area has been well developed. While most of the studies on predation have focused on animal or insect predation, some have also ex-amined carnivorous plants and carnivorous fungi that prey on animals, especially insects and nematodes [10,11]. With regard to fungal predators, although studies on taxonomy, evolution, and predatory mechanisms have been reported [12,13], there is still a lack of ecological dynamic models describing the unique predatory interaction.…”
mentioning
confidence: 99%